Ultrashort Peptides and Gold Nanoparticles: Influence of Constrained Amino Acids on Colloidal Stability - Locarno, Silvia; Bucci, Raffaella; Impresari, Elisa; Gelmi, Maria Luisa; Pellegrino, Sara; Clerici, Francesca (Frontiers in Chemistry, 2021)
Poor colloidal stability of gold nanoparticles (AuNPs) in physiological environments remains one of the major limitations that contribute to their difficult translation from bench to clinic. For this reason, an active research field is the development of molecules able to hamper AuNPs aggregation tendency in physiological environments. In this context, synthetic peptides are gaining an increased interest as an alternative to the use of biomacromolecules and polymers, due to their easiness of synthesis and their profitable pharmacokinetic profile. In this work, we reported on the use of ultrashort peptides containing conformationally constrained amino acids (AAs) for the stabilization of AuNPs. A small library of non-natural self-assembled oligopeptides were synthesized and used to functionalize spherical AuNPs of 20 nm diameter, via the ligand exchange method. The aim was to investigate the role of the constrained AA, the anchor point (at C- or N-terminus) and the peptide length on their potential use as gold binding motif. Ultrashort Aib containing peptides were identified as effective tools for AuNPs colloidal stabilization. Furthermore, peptide coated AuNPs were found to be storable as powders without losing the stabilization properties once re-dispersed in water. Finally, the possibility to exploit the developed systems for binding proteins via molecular recognition was also evaluated using biotin as model.